2000
DOI: 10.1037/0882-7974.15.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Role-specific feelings of control and mortality.

Abstract: The purpose of this study is to examine the impact of 2 different measures of personal control on mortality in late life. The 1st reflects control over the 3 roles that are most important to elderly study participants. The 2nd is a global measure that assesses control over life as a whole. Data provided by a nationwide survey of older adults (N = 884) indicate that feelings of control over the single most important role significantly reduce the odds of dying. In contrast, control over the 2nd and 3rd most impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 74 publications
3
67
0
2
Order By: Relevance
“…In contrast, Krause and Shaw (2000) found that feelings of control over life as a whole were not related to mortality among elderly study participants. Further inquiry of this issue is, thus, warranted.…”
Section: Discussionmentioning
confidence: 39%
“…In contrast, Krause and Shaw (2000) found that feelings of control over life as a whole were not related to mortality among elderly study participants. Further inquiry of this issue is, thus, warranted.…”
Section: Discussionmentioning
confidence: 39%
“…For example, several studies have shown that lower feelings of control and mastery predict all-cause mortality over follow-ups of 2.5 years (Penninx et al, 1997), 4.8 years (Surtees, Wainwright, Luben, Khaw, & Day, 2006), and 11 years (Surtees et al, 2010). In a similar vein, Krause and Shaw (2000) reported that greater feelings of control in one's most salient role in life (but not global feelings of control) were predictive of all-cause 6-year survival. When targeting specific causes of death, the evidence suggests that perceived control is particularly associated with cardiovascular mortality, but not with cancer mortality (Surtees et al, 2006(Surtees et al, , 2010.…”
Section: Health Outcomes Of Perceived Controlmentioning
confidence: 73%
“…We argue that the effects of perceived control and associated (healthrelated) behaviors need time to evolve and accumulate. As a consequence then, the beneficial effects of greater perceived control or the detrimental effects of low perceived control should be more pronounced and visible in later phases of life relative to earlier phases (see Elder & Johnson, 2003;Fauth et al, 2007;Krause & Shaw, 2000). Consistent with this conceptual reasoning, Infurna, Gerstorf, and Zarit (in press) found in the adult lifespan sample (ages 25 -96) of the Americans' Changing Lives study that perceived control was predictive of subsequent health changes in old age, but not in midlife.…”
Section: Health Outcomes Of Perceived Controlmentioning
confidence: 99%
“…Some studies have reported protective effects of control on morbidity and mortality, although the effects are not consistent across studies (DeVellis & DeVellis, 2001). Krause and Shaw (2000) suggested that some of the inconsistency in the literature reflects the difference between general control vs. situation-or role-specific control. In their study, global control did not predict mortality, but feelings of control in the most important social role did predict longevity.…”
Section: Protective Factorsmentioning
confidence: 99%